Deleuze: do pensamento trágico à nova imagem do pensamento em Nietzsche - Sousa, Péricles Pereira de (Universidade Federal de São Carlos, 2004)
This study aims at following Deleuzes s reflections about Nietzsche, assuming as the reading object the book Nietzsche and the Philosophy (1962). From the first pages, Deleuze asserts that Nietzsche is responsible for inscribing in the History of Philosophy a new image of thinking, consonant with a new image of the philosopher. Especially on the third chapter, this idea gains profundity, for Deleuze not only discovers in Nietzsche a project of critical nature but also turns it against Kant. In a few words, Deleuze believes to find in Nietzsche s Genealogy of Moral a sort of answer to the Critique of Pure Reason, since Kant did not manage to carry out his critical undertaking fully, for not having considered the problems in terms of values. Nietzsche is the major responsible for such feat. To Deleuze, the Kantian critique is just a caricature of the real critique. Although these are the most important ideas, Deleuze was followed as a whole, trying to keep the attention to the whole of his reflections in the most important chapters for this essay. In short, it is about a flight which starts with the tragic thinking and ends in the critique.
Keywords: História da filosofia; Pensamento trágico; Crítica kantiana; Caricatura da crítica; Crítica nietzscheana; Nova imagem do pensamento; Tragic thinking; Kantian critic; Caricature of critique; Nietzschean critique; New image of thinking; CIENCIAS HUMANAS::FILOSOFIA